2017
DOI: 10.1159/000479523
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating Cell-Free DNA Levels in Patients with Metastatic Renal Cell Carcinoma

Abstract: Background: Limited data about biomarkers are available to predict the outcomes of targeted therapy in metastatic renal cell carcinoma (mRCC). Circulating cell-free DNA (CFD) is elevated in various cancers. Patients and Methods: We performed a prospective study of patients with mRCC who received targeted therapy in the Soroka Medical Center between 2013 and 2015. CFD levels were measured using a simple fluorometric assay. Blood samples for CFD were collected before treatment and at weeks 1, 4, 12, 18, and 24 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Few studies have explored the role of cfDNA in monitoring therapeutic efficacy in mRCC [ 61 , 69 , 70 , 89 ]. A report by Fang et al on patients with mRCC showed a correlation between higher levels of plasma cfDNA and poor response to sorafenib [ 61 ].…”
Section: Applications Of Cfdna Analysis In Rccmentioning
confidence: 99%
“…Few studies have explored the role of cfDNA in monitoring therapeutic efficacy in mRCC [ 61 , 69 , 70 , 89 ]. A report by Fang et al on patients with mRCC showed a correlation between higher levels of plasma cfDNA and poor response to sorafenib [ 61 ].…”
Section: Applications Of Cfdna Analysis In Rccmentioning
confidence: 99%
“…Nowadays, several measurements of cfDNA characteristics are used in cancer patient liquid biopsies: SNP analysis of proto-oncogenes and onco-suppressors, changes in the pattern of DNA methylation, and the abundance of oncogene fragments and other specific fragments of tumor-derived DNA microsatellites, tandem repeats, and mobile genetic elements. [1][2][3] Although attempts have been made to use cfDNAs as indicators of cancer development, based on the content of specific DNA sequences in the blood, the low sensitivity of cfDNA measurement methods, and failure to apply developed markers for early-stage tumor development, has significantly limited the clinical application of this analysis. 4,5 On the other hand, increases in microsatellite content, tandem repeats, and mobile genetic elements are commonly detected in the early stages of cancer, both in experimental tumor models and patients, causing researchers to consider these sequences as potential markers for prognosis, as well as factors in disease progression and cure.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-free DNA is shed from apoptotic and necrotic cells into the blood stream ( 66 ). Since its first identification in cancer patients ( 67 ), it has been investigated as both a diagnostic ( 68 , 69 ) and prognostic cancer ( 70 , 71 ) biomarker in RCC and other cancers ( 72–75 ). However, cell-free DNA is not yet clinically validated in RCC.…”
Section: Discussionmentioning
confidence: 99%